An investigation into the stress-permeability relationship of coals and flow patterns around working longwall faces - Durucan, S. (1981)
This research aimed to establish a physical relationship between applied stress and permeabilities of different coals. Seven different coals, ranging from medium volatile to high volatile bituminous, were tested for stress-permeability relationship under simulated subsurface stress conditions.